Orders of the Folk Architecture of Surkhandarya Region - Shukurullo Yunusov (International Journal of Advanced Science and Technology, 2020)
This article explores the history of Surkhandarya architecture situated in southern Uzbekistan and the stages of formation of its order system. The research has been carried out on the stages of applying the order system in the intact, ancient and preserved residential and public buildings of the region, and their compositional solutions.